INFORMATION TECHNOLOGIES AND OSINT SYSTEMS AS TOOLS FOR AUTOMATION AND CYBERNETIC GOVERNANCE IN THE GLOBAL INFORMATION SPACE - Reinska, Viktoriia (European Science, 2025)
The article examines information technologies and OSINT (Open Source Intelligence) systems as an integral tool for automation and cybernetic governance in the global information space. The study substantiates the role of OSINT as a component of modern inf